The number of bank relationships of SMEs: A disaggregated analysis for the Swiss loan market - Doris Neuberger; Christoph Schacht (Universität Rostock, Institut für Volkswirtschaftslehre, 2005)
The present paper investigates the number of bank relationships of small and medium-sized enterprises in Switzerland using survey data from 1996 and 2002. We differentiate between overall bank relationships and lending relationships and disaggregate the loan market with respect to firm sizes, industries and banking groups. On average, bank lending declined, while the role of housebank relationships increased in 1996-2002. The development of the number of bank relationships seems to have been demand-driven as well as supply-driven for medium-sized firms, but only supply-driven for very small and small firms. Supply-side reductions resulted from the merger between two big banks and changes in credit risk management at major banks.
Keywords: G21; G32; 330; relationship lending; housebank; loan market structure; multiple banks